Avaliação da atividade antifúngica in vitro da fração líquida da pirólise de esterco bovino : fonte alternativa de fungicidas - Ramos, Maria Lucileide Nogueira Santos (2019)
About one third of food for human consumption is lost or wasted, representing around 1 billion tons per year. Among the organisms that cause diseases in plants, phytopathogenic fungi are the most destructive and impose huge damage to natural systems and production. Currently synthetic fungicides are the main means of controlling diseases caused by fungi, however, the continuous and systematic use of fungicides may select fungi with multiple resistance. In this context, alternative fungicides emerge as a promising tool for disease control in plants and the thermal conversion of lignocellulosic biomass can contribute to this field. In this work, the bio-oil of cattle manure produced at 400, 500 and 600 ºC, as well as their respective aqueous fractions, had their antifungal activities evaluated in vitro against phytopathogenic fungi as Fusarium solani and Lasiodiplodia theobromae. The best activities were observed for the aqueous fraction produced at 400 °C, obtaining a fungistatic potential of 100% at the concentration of 4000 μg mL-1 as well as a potential fungicide for the fungi Lasiodiplodia theobromae and Fusarium solani. The bio-oils produced at all studied temperatures had presented fungistatic potential, but when subjected to analysis of variance and characterization by Gas Chromatography/Mass Spectrometry (GC/MS) and Mass Spectrometry with Fourier Transform (FT-MS) did not present significant differences as to its composition, presenting mainly oxygenated class of compounds. The characterization by GC/MS presented the phenolic compounds as main constituents of the bio-oils, and the increase of the pyrolysis temperature provided a relative increase of the relative area of these compounds peaks. This previous study demonstrated the potential of the use of bio-oil and the aqueous fraction derived from the thermal conversion of cattle manure as an alternative source of fungicides, aiming to minimize the pollution caused by the proposed biomass, adding value to the products, expanding the range of applications and minimizing losses in food production.